The Role of the Office of Religious Affairs in the Prevention of Underage Marriage in the perspective of Maqashid Syariah - Rahmadhani, Layla Rizki; Attamimi, Faisal; Hanafi, Suhri (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC LAW AND SOCIETY, 2023)
This study discuss role of the Office of Religious Affairs in preventing underage marriages from the perspective of maqashid syari’ah. This study used qualitative approach with a case study methodology. Both primary and secondary data were utilized in this study, employing data collection techniques such as observation, in-depth interviews, and written document analysis. The findings of this study show that the role of the religious office in preventing underage marriages involves the implementation of two preventive activities, namely, religious study sessions (majelis ta’lim) and the formation of mosque youth groups. The role of the office in preventing underage marriages should be further enhanced, advocating for the optimal implementation of religious study programs and the formation of mosque youth groups in prevention efforts. The challenge factors include insufficient funding and a lack of community attention. From the maqashid syari’ah perspective, the role of the office in preventing underage marriages does not align with the Sharia objectives in preserving lineage (hifz nazhl). This misalignment arises because the office role falls short of regulating marriages in accordance with the dictates of Sharia and the Marriage Law regarding age regulations. Implications of this study call for the necessity of enhancing the office role in preventing underage marriages to align with maqashid syari’ah universally.